Environmental impact of green house gas emissions from the tea industries of northeastern states of India - Aditya, Kaustav; Kumar, Raju; Bharti,; Sanyal, S. (Frontiers in Sustainable Food Systems, 2023)
Motivation Tea, derived from the Camellia sinensis plant, holds the position of being the most widely consumed manufactured beverage globally. Its cultivation necessitates specific agro-climatic conditions, leading to its production being confined to select regions, notably including India. India contributes about 20.81% to the world’s tea output. The production and processing of tea leaves to final product consume energy in terms of machinery, fertilizer, irrigation etc. The energy consumption involved in tea production is a pressing concern, given the associated high costs and CO2 emissions resulting from fossil fuel usage. To achieve a net-zero carbon balance, there is need to pay attention towards promoting renewable energy technologies as a means to mitigate the CO2 emissions stemming from fossil fuels in India’s tea sector. Objectives Aligned with the objective of sustainability through the integration of renewable energy sources, a pilot study was conducted in the primary tea-growing regions of northeastern India during 2021–22. The primary aims of this study were twofold: to gauge the quantity of CO2 emissions originating from conventional energy sources and to explore the feasibility of incorporating renewable energy sources as viable substitutes. Data and methods Data on various inputs used in tea production were collected from Assam and West Bengal states of India by using a stratified random sampling method with equal probability and without replacement. Results The findings of this investigation underscore a noteworthy potential for the adoption of renewable energy, particularly solar energy, within the tea estates situated in the north eastern region of India. Such a transition would yield benefits for both the tea estates themselves and the overall environment.